Development of Media Smart Apps Creator Integrated Problem-Based Learning Model Learning on Reaction Rate Material - Azmi, Nurul; Muchtar, Zainuddin (UNDIKMA, 2024)
This research aims to produce an Integrated learning media product using Problem-Based Learning smart apps creator application with modelsÂ Thiagarajan's 4D development. Based on research carried out, media expert opinion, educator response, participant response students towards integrated learning media Problem-Based Learning using the smart apps creator application gets criteria very worthy with an average media expert assessment score of 96.08%, educator response assessment 95.05%, and Student response assessment was 80.2%. The results of this research show that interactive learning media is based on Problem-Based Learning useing the smart apps creator application on the speed material point reactions can be used as a learning medium.